Energy and angular momentum of the gravitational field in the teleparallel geometry - Maluf, J. W.; Da Rocha-Neto, J. F. [UNESP]; Toribio, T. M L; Castello-Branco, K. H. (My University, 2002)
The Hamiltonian formulation of the teleparallel equivalent of general relativity is considered. Definitions of energy, momentum and angular momentum of the gravitational field arise from the integral form of the constraint equations of the theory. In particular, the gravitational energy-momentum is given by the integral of scalar densities over a three-dimensional spacelike hypersurface. The definition for the gravitational energy is investigated in the context of the Kerr black hole. In the evaluation of the energy contained within the external event horizon of the Kerr black hole, we obtain a value strikingly close to the irreducible mass of the latter. The gravitational angular momentum is evaluated for the gravitational field of a thin, slowly rotating mass shell. © 2002 The American Physical Society.
Keywords: density; energy; geometry; gravity; mass; mathematical model; quantum theory; rotation